1989
DOI: 10.1079/bjn19890153
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in Asian Muslim pregnant mothers observing the Ramadan fast in Britain

Abstract: 1. Metabolic changes associated with Ramadan fasting were studied in eleven Asian pregnant mothers. This was compared with a group of control mothers undergoing a normal physiological fast.2. At the end of the Ramadan fast day there was a significant fall in glucose, insulin, lactate and carnitine, and a rise in triglyceride, non-esterified fatty acid and 3-hydroxybutyrate. When compared with the control group, none of the Ramadan mothers had a completely normal set of biochemical values at the end of the fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 12 publications
3
73
1
1
Order By: Relevance
“…Arab (2004) found that 31 percent of pregnant women in Iran had ketonuria, whereas 61 percent had hypoglycemia before breaking their fast. In the UK and West Africa, Prentice et al (1983) and Malhotra et al (1989) measured unambiguous signs of accelerated starvation in Ramadan among pregnant women who were fasting.…”
Section: Evidence On First Stage Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arab (2004) found that 31 percent of pregnant women in Iran had ketonuria, whereas 61 percent had hypoglycemia before breaking their fast. In the UK and West Africa, Prentice et al (1983) and Malhotra et al (1989) measured unambiguous signs of accelerated starvation in Ramadan among pregnant women who were fasting.…”
Section: Evidence On First Stage Effectsmentioning
confidence: 99%
“…during pregnancy can have an 'accelerated starvation' effect on the mother, leading to fetal damage (Malhotra et al, 1989;Mirghani et al, 2005;Prentice et al, 1983). Barker's fetal origins hypothesis (Barker, 1995) implies that fetal damage in turn may have long-term impacts on health, cognition and socio-economic outcomes (Almond, 2006;Almond and Currie, 2011;Currie and Vogl, 2012).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Accelerated starvation is noticed in pregnant women compared with nonpregnant women after only 12 hours of fasting. 6 After a period of fasting for 13 hours or more, maternal corticotrophin-releasing hormone is elevated compared with those without food for periods less than 13 hours.…”
Section: Introductionmentioning
confidence: 99%
“…7 There are few studies to discuss Ramadan fasting and its effect on neonatal health. 10,11 Malhotra et al compared metabolic changes in 11 Ramadan-fasted and 11 overnight-fasted pregnant women and none of the Ramadan-fasted mothers had a completely normal set of biochemical values at the end of the fast day. Nevertheless, they did not find any difference between pregnancy outcomes of these two small groups of mothers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation